Evaluation of the Presentation of Newly Diagnosed Type 1 Diabetes Mellitus in Children During and After the COVID-19 Pandemic - Semine Özdemir Dilek; Fatma Özgüç Çömlek (Genel Tıp Dergisi)
Background: The COVID-19 pandemic has been a global health problem with high morbidity and mortality. In this study, it was aimed to compare the clinical and laboratory findings of patients diagnosed with type 1 diabetes(T1D) during the pandemic and after the pandemic. Method: This is a 30-month, single-center, cross-sectional study. Between October 2020 and December 2021 was defined as the pandemic period, and between January 2022 and March 2023 as the post-pandemic period. The clinical and laboratory parameters of the newly diagnosed T1D patients who applied in these two time periods were compared. Results: While 87 patients were diagnosed during the pandemic period, 86 patients were diagnosed during the post-pandemic period. The rate of male patients diagnosed during the pandemic period was significantly higher (56%, 36%, respectively, p=0.007). Anti-islet Cell antibody (ICA) positivity was statistically significantly higher in those diagnosed during the pandemic period. (52.6%, 18.6%, respectively, p<0.001). There was no difference between the groups in terms of hemoglobin A1C, thyroid autoantibodies and tissue transglutaminase antibodies (p>0.05).C peptide levels were significantly lower in those diagnosed during the pandemic period (0.39±0.4, 0.63±0.6, respectively, p=0.021). Admissions with severe acidosis were more common during the pandemic than those admitted after the pandemic (29.9%, 16.3%, respectively, p=0.151). Conclusions: The numbers of children with T1D newly diagnosed in a secondary health center were similar during and after the pandemic. In the pandemic period, admissions with autoantibody positivity, low C-peptide and severe acidosis were more common.